2020
DOI: 10.1186/s12872-020-01722-8
|View full text |Cite
|
Sign up to set email alerts
|

Aortic stiffness and central hemodynamics in treatment-naïve HIV infection: a cross-sectional study

Abstract: Background Human immunodeficiency virus (HIV) infection is associated with a greater risk of cardiovascular disease (CVD). HIV infection causes a chronic inflammatory state and increases oxidative stress which can cause endothelial dysfunction and arterial stiffness. Aortic stiffness measured by carotid femoral-pulse wave velocity (cfPWV) and central hemodynamics are independent cardiovascular risk factors and have the prognostic ability for CVD. We assessed cfPWV and central hemodynamics in yo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 69 publications
(79 reference statements)
0
9
0
Order By: Relevance
“…There is strong accumulated evidence indicating a decrease in arterial stiffness following acute aerobic exercise (Mutter et al, 2017;Pierce et al, 2018). Arterial stiffness depends on several factors, such as endothelial function, smooth muscular vascular tone, and structural features (Martinez-Ayala et al, 2020). It has been proposed that a relaxation of vascular smooth muscle transfers stress from the less extensive collagen fibers to elastin, which could partially account for decreases in arterial stiffness after exercise (Mutter et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is strong accumulated evidence indicating a decrease in arterial stiffness following acute aerobic exercise (Mutter et al, 2017;Pierce et al, 2018). Arterial stiffness depends on several factors, such as endothelial function, smooth muscular vascular tone, and structural features (Martinez-Ayala et al, 2020). It has been proposed that a relaxation of vascular smooth muscle transfers stress from the less extensive collagen fibers to elastin, which could partially account for decreases in arterial stiffness after exercise (Mutter et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that a relaxation of vascular smooth muscle transfers stress from the less extensive collagen fibers to elastin, which could partially account for decreases in arterial stiffness after exercise (Mutter et al, 2017). Evidence demonstrates that changes in immune activity due to HIV infection may increase the pulse wave velocity (Boccara et al, 2006;Rider et al, 2014), disrupting the activity of the matrix metalloproteinase (MMPs) (Misse et al, 2001) and degrading collagen, elastin, laminin, and fibrillin within the arterial wall (Martinez-Ayala et al, 2020). The consequent increasing in vascular resistance limits the vasodilation response during exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, reduced aoBP levels in the setting of similar baBP in PLWHIV would suggest that both HIV infection and/or highly active antiretroviral therapy play a role in hemodynamics, with differential effects on different locations of the vasculature (central vs. peripheral vessels). As was discussed by Martínez-Ayala et al ( 12 ) lower aoBP levels may be caused by a peripheral vasodilation of small and medium-sized arteries, possibly induced by prostaglandins and other inflammatory cytokines associated with the chronic HIV infection. The vasodilation effect on peripheral reflection sites (e.g., arterial bifurcations) might cause a reduced Pb and Pb/Pf, and a reduced contribution to aoSBP.…”
Section: Discussionmentioning
confidence: 86%
“…More precisely, there are scarce, and above all, controversial data on whether HIV infection is independently associated with aortic blood pressure (aoBP) levels and waveform-derived indexes. Previous studies have reported that both aoBP and some waveform-derived indexes were either elevated ( 9 , 10 ), unchanged ( 9 , 11 ), or even reduced ( 12 14 ) in PLWHIV compared to HIV- subjects.…”
Section: Introductionmentioning
confidence: 96%
“…Studies from high-income settings have shown that PWH have less favorable carotid intima-media thickness, shear strain, presence of plaque, and pulse wave velocity parameters [ 25 , 26 ]. Higher pulse wave velocity and central pulse pressure measures are present in untreated PWH compared to HIV-negative adults [ 27 ]. Conversely, one South African study reported no differences in pulse wave velocity and carotid intima-media thickness between PWH and uninfected controls.…”
Section: Discussionmentioning
confidence: 99%